EFEKTIVITAS MEDIA KULTUR YANG BERBEDA TERHADAP KUALITAS DAN KUANTITAS MAGGOT (Hermetia illucens) SEBAGAI PAKAN ALAMI - Masliana, Masliana; Islama, Dini; Diansyah, Sufal; Muliyana, Agusriati (JURNAL AKUAKULTURA, 2022)
This study aims to determine the effect of using different culture media on the quality and quantity of maggot. This study used a completely randomized design consisting of four treatments and three replications. The culture media used consisted of; P0 (control) = 1000 gr of tofu pulp, P1 = 1000 gr of tofu pulp + 500 gr of bran, P2 = 1000 gr of tofu pulp + 500 gr of tofu pulp, P3 = 1000 gr of tofu pulp + 500 grams of chicken manure. The parameters observed were population, weight, body length and the results of the proximate maggot test. The results of the analysis of variance (ANOVA) showed that the use of different culture media had a significant effect on the quality and quantity of maggot. The best culture media to increase maggot growth was found in P3 with a population value of 23,000 ind, a weight of 0.74 gr, and a length of 15.8 mm. Based on the results of the proximate test, the best maggot quality was also found in P3 which contained a protein content of 32.48%.